The development of doped radiosensitive glass - Bradley, D. A.; Hugtenburg, Richard P.; Hashim, Suhairul; Okoya, O. O.; Yusof, A. L.; Mat Hassan, A. Aziz; Ramli, Ahmad Termizi; Wagiran, Husin (2007)
For a range of industrial and medical situations there exists need for sensitive, robust high spatial resolution systems for radiation measurements. Our overall focus is on the development of doped silica-glass thermoluminescent dosimeters (TLD) with a view towards improving upon the thermoluminescence (TL) yield of commercially produced optical fibers. In baseline studies of the latter, as detailed herein, measurements have been conducted using Ge-doped communication fibers, employing sources of irradiation including bremsstrahlung x-rays (produced by a nominal accelerating potential of 50 kVp), alpha particles from an 241Am source (predominant emission 5.486 MeV) and protons of energy 2.5 MeV provided by an ion beam source. Present studies, also including elemental analysis via the PIXE and RBS techniques, permit comparison with higher TL yield doped glasses previously made by this group via the sol-gel technique and characterized in part using a range of synchrotron techniques.